The Effects of Microalgae as Live Food for Brachionus plicatilis (Rotifer) in Intensive Culture System - Abdull Razak Abd Rahman; Zaidi Che Cob; Zainoddin Jamari; Abdul Majid Mohamed; Tatsuki Toda; Othman Haji Ross (Tropical Life Sciences Research, 2018)
Brachionus plicatilis is used to feed fish and crustacean larvae in the aquaculture industry. It is well established that the type of microalgae may influence rotifer production. This experiment was conducted to determine the effect of five different locally available microalgae species at Fisheries Research Institute (FRI), Kampung Pulau Sayak, Kedah, Malaysia on the instantaneous growth rate (?) of rotifer. Nannochloris sp., Tetraselmis sp., Isochrysis sp., Chlorella sp., and Nannochloropsis sp. were used as feed at different algae densities (0.1, 0.3, 0.7 and 1.5 Å~ 106 cells/ml) and culture volumes (20, 70 and 210 ml). At algae densities ranging from 0.3 to 1.5 Å~ 106 cells/ml, an average ? value of more than 0.90 per day were recorded for all algae species. However, at density of 0.1 Å~ 106 cells/ml, only Tetraselmis sp. resulted in the significantly highest ? value compared with others (p < 0.05). In terms of volume, smaller culture volume of Tetraselmis sp. (20 ml) showed significantly higher ? compared with higher volume (70 and 210 ml cultures). Brachionus plicatilis digunakan untuk memberi makan ikan dan larva krustacea dalam industri akuakultur. Telah termaktub bahawa jenis mikroalga boleh mempengaruhi pengeluaran rotifer. Eksperimen ini dijalankan untuk menentukan kesan spesis mikroalga yang terdapat di Institut Penyelidikan Perikanan (FRI), Kampung Pulau Sayak, Kedah, Malaysia pada kadar pertumbuhan segera (?) rotifer. Nannochloris sp., Tetraselmis sp., Isochrysis sp., Chlorella sp. dan Nannochloropsis sp. digunakan sebagai makanan pada kepadatan alga yang berbeza (0.1, 0.3, 0.7 dan 1.5 Å~ 106 sel/ml) dan jumlah kultur (20, 70 dan 210 ml). Pada kepadatan alga antara 0.3 hingga 1.5 × 106 sel/ml, nilai purata ? lebih daripada 0.90 sehari dicatatkan untuk semua spesies alga. Walau bagaimanapun, pada ketumpatan 0.1 Å~ 106 sel/ml, hanya Tetraselmis sp. menghasilkan nilai ? yang paling tinggi berbanding dengan yang lain (p < 0.05). Dari segi isipadu, isipadu kultur Tetraselmis sp. yang lebih kecil (20 ml) menunjukkan ? yang lebih tinggi berbanding dengan isipadu kultur tertinggi (kultur 70 dan 210 ml).